Mean-field approximation for finite nuclei and nuclear matter - S. Shlomo (Ядерна фізика та енергетика)
We discuss a realistic case of fitting the values of the Skyrme parameters to an extensive set of experimental data on the ground-state properties of many nuclei ranging from normal to exotic ones. We include, in particular, the radii for valence neutron orbits and the breathing-mode energies for several nuclei. We further constrain the values of the Skyrme parameters by requiring positive values for the slope of the symmetry energy S, the enhancement factor, κ associated with the isovector giant dipole resonance, and the Landau parameter G'0 . We also present results of Hartree-Fock based random phase approximation for the excitation strength function of the breathing mode and discuss the current status of the nuclear matter incompressibility coefficient.